Ways animals sleep - McCauley, Jane R., 1947- ([Washington, D.C.] : National Geographic Society, 1983)
Describes the different methods of sleep of a variety of mammals, fish, insects, and birds. Includes such details as postures of sleep, location, duration, and special adaptation to habitat.
Some ill. on lining papers.
Keywords: Sleep behavior in animals -- Juvenile literature; Animals -- Sleep behavior; Sleep; Animals -- Habits and behavior